P038 Let's look at coxitis features in enthesitis-related arthritis population. (11th November 2021) - Yasmine, Makhlouf; Ferjani, Hanene; Maatallah, Kaouther; Triki, Wafa; Ben Nessib, Dorra; Kaffel, Dhia; Hamdi, Wafa
Abstract: Background: Enthesitis-related arthritis (ERA) is a defined juvenile idiopathic arthritis subtypes, which presents with enthesitis, arthritis and axial skeleton involvement. ∼20–50% of JIA patients have hip involvement within 1–6 years of diagnosis onset [1]. The frequency of coxitis in ERA category is not recognized. The aim of this study was to assess coxitis features and its management in ERA population. Methods: A retrospective study including children with ERA according to the International League of Associations for Rheumatology (ILAR). Data recorded included sociodemographic features, disease characteristics (disease duration, extra-articular manifestations, and presence of HLAB27) as well as treatment modalities. Regarding coxitis, we collected radiographs, ultrasound (US) and magnetic resonance imaging (MRI) of the hip when performed. Coxitis was defined by clinical (limited range of motion) and/or radiographic findings (destruction, synovitis, bone marrow oedema). Results: The study included 51 patients with ERA. There was a male predominance (78.4%). The mean age of onset of the disease was 12.2 years [6–16]. The mean current age was 24.3 years old [9–59]. A family history of spondyloarthritis was found in 26.8% of cases. A positive HLAB27 was reported in 85.7% of cases. The distribution of extra-articular manifestations (37.5%) was as follows: ocular ( n  = 8), cardiovascular ( n  = 2), gastrointestinal ( n  = 1), pulmonary ( n  = 4). A peripheral onset was found in 39% and a peripheral and axial onset was reported in 42% of patients. Hip involvement was found in 78.4% of the patients and revealed the disease in 43% of cases. The mean delay between disease onset and coxitis was 4.5 years [0–34]. Coxitis was bilateral and destructive in 82.5% and 51% of cases respectively. The most limited range of motion was the internal rotation (68%), followed by hip flexion (48%) and the external rotation (43.2%). In patients with normal hip radiography ( n  = 8), US or MRI depicted early changes in 75% of cases. Hip replacement was noted in ten patients and was bilateral in 70% of cases. Regarding treatment modalities, NSAIDs and csDMARD (MTX n  = 14, SLZ n  = 8, biologics n  = 2) were prescribed in 76.4% and 52% respectively. Most of the patients had physical therapy (88%) and 23.5% of them had intra-articular corticoid injection. Twenty-six percent of the patients had hip replacement. Conclusion: Our study showed a high prevalence of coxitis among ERA patients. There is a need to further optimize therapeutic strategies for such patients.